Nanocomposites of natural rubber and polyaniline-modified cellulose nanofibrils - Silva, M. J. [UNESP]; Sanches, A. O. [UNESP]; Medeiros, E. S.; Mattoso, L. H. C.; McMahan, C. M.; Malmonge, J. A. [UNESP] (Springer, 2014)
Cellulose nanofibrils (CNF) were isolated from cotton microfibrils (CM) by acid hydrolysis and coated with polyaniline (PANI) by in situ polymerization of aniline onto CNF in the presence of hydrochloride acid and ammonium peroxydisulfate to produce CNF/PANI. Nanocomposites of natural rubber (NR) reinforced with CNF and CNF/PANI were obtained by casting/evaporation method. TG analyses showed that coating CNF with PANI resulted in a material with better thermal stability since PANI acted as a protective barrier against cellulose degradation. Nanocomposites and natural rubber showed the same thermal profiles to 200 A degrees C, partly due to the relatively lower amount of CNF/PANI added as compared to conventional composites. On the other hand, mechanical properties of natural rubber were significantly improved with nanofibrils incorporation, i.e., Young's modulus and tensile strength were higher for NR/CNF than NR/CNF/PANI nanocomposites. The electrical conductivity of natural rubber increased five orders of magnitude for NR with the addition of 10 mass% CNF/PANI. A partial PANI dedoping might be responsible for the low electrical conductivity of the nanocomposites.
Keywords: Cellulose nanofibrils; Cotton cellulose; Polyaniline; Natural rubber